Validity and reliability of the Malay version of the comprehensive feeding practices questionnaire (CFPQ-M) tested among mothers of school children in the Klang Valley, Malaysia - Wong, Yoke Wei (2012)
Increasing prevalence of childhood obesity has become the in ealth issue in Malaysia. There is a need to have improved public health preventive programs which should be started in the early childhood. Parents could be described as an obesigenic agent for children. Their feeding practices have been found to be related to childhood obesity. Hence, a valid and reliable instrument to examine parental feedi ng practices is needed. The objective of this study was to examine the validity and reliability of the Comprehensive Feeding Practices Questionnaire (CFPQ), an instrument that assesses child-feeding practices. The Malay version CFPQ (CFPQ-M) was tested among 397 mothers of primary school children (Year 1-3) CFPQ-M contained 12 subscales on feeding practices including monitoring (mean=3.36±0.86), emotion regulation (mean=2.04±0.75), food as reward (mean=2.72±1.12), child control (mean =2.57±0.63), modelling (mean=4.12±0.76), restriction for weight control (mean=3.34±0.95), restriction for health reasons (mean=3.86±1.20), teaching about nutrition (mean=4.24±0.80), encouraging balance and variety (mean=4.02±0.74), pressure to eat (mean score=2.89±1.00), healthy environment (mean=4.26±0.83) and involvement (mean=3.88±0.84). A series of tests including confirmatory factor analysis (CFA) were used to examine the psychometric properties of the clinical instrument. A hypothesized model was examined and revised which was then respecified in order to get the best fitted model. A series of fit indices were used to determine a good fit model. Of 49 items, 39 items with loading factors >0.40 were retained. The CFA revealed that the final model (twelve-factor model with 39 items and 2 error covariances) displayed the best fit for our sample (Chi-square=1147, df=634, p<.05, CFI=0.900, RMSEA=0.045, SRMR=0.058). The Cronbach’s alphas for the subscales ranged from 0.45 to 0.90. Convergent validity was obtained for most of the CFPQ-M subscales by assessing the relationships between mean scores of the subscales and child’s dietary fat intake over the past seven days, which was obtained using the self-modified Patient-centered Assessment and Counseling for Exercise Plus Nutrition (PACE+) dietary fat screener. The variables were correlated asfrom schools in Selangor, Kuala Lumpur and Putrajaya. expected (all r>0.10, p<0.05). One week test-retest reliability of the instrument was tested using paired-sample t-test and the results were acceptable (t ranges from -1.26 to 0.86, all p>0.05). A valid and reliable instrument is very important as it helps to explore many possible related researches and assure the quality of the data and results. The importance of the present study was further supported by a high prevalence of childhood obesity (13.9%) in the present study. This study showed that the translated instrument with some modifications was valid and reliable. The instrument will help researchers to better understand the relationships between parental feeding practices and child’s dietary intake and weight status. Various of interventions to reduce childhood obesity can be organized in order to prevent the health problems associated with childhood obesity.